Use of residual glycerin and glycerol in biopolymer preparation - Rezende, Dennis Júnior Lara Faleiro de; Sarrouh, Boutros; Naves, Fabiano Luiz; Lofrano, Renata Carolina Zanetti (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Residual glycerin, a co-product obtained in the biodiesel production by transesterification reaction, has been generated in great quantities in the last decade due to the increase in the demand of this biofuel. Therefore, researches related to the production of high added value and environmental friendly materials using residual glycerin are fundamental for an appropriate destination of this waste. In this context, the present study aims on the reuse of the glycerin co-product in the synthesis of poly(glycerol citrate) biopolymer. Polymerization reactions were studied using citric acid, residual glycerin without pre-treatment and ZnCl2 as catalyst. Conversion rates of 58.2 % were obtained in 120 min of reaction time, such results shows a promising potential in producing a biodegradable biopolymer using law cost raw material.